PENGARUH IMPLEMENTASI SISTEM INFORMASI KEUANGAN DAERAH DAN KINERJA PEGAWAI: KUALITAS INFORMASI LAPORAN KEUANGAN SEBAGAI VARIABEL INTERVENING (STUDI EMPIRIS PADA SATUAN KERJA PERANGKAT DAERAH KABUPATEN BANYUMAS - Dona Primasari (Optimum: Jurnal Ekonomi dan Pembangunan, 2013)
The objective of this research is to analyze the influence of effectiveness of regional financial information system to officer performance,with the quality of information of financial report as intervening variable.Data was collected by 61 officer of SKPD Banyumas. The analysis method used is AMOS ver.18.00 analysis, The result of the analysis shows: (1) a strong influence between effectiveness of regional financial information system to officer performance (2) a moderate influence between effectiveness of regional financial information system to officer performance with the quality of information of financial report.